Prevalence of and Risk Factors for Anxiety and Depressive Disorders after Traumatic Brain Injury: A Systematic Review - Scholten, Annemieke C.; Haagsma, Juanita A.; Cnossen, Maryse C.; Olff, Miranda; van Beeck, Ed F.; Polinder, Suzanne (Journal of neurotrauma, 2016)
This review examined pre- and post-injury prevalence of, and risk factors for, anxiety disorders and depressive disorders after traumatic brain injury (TBI), based on evidence from structured diagnostic interviews. A systematic literature search was conducted in EMBASE, MEDLINE, Cochrane Central, PubMed, PsycINFO, and Google Scholar. We identified studies in civilian adults with TBI reporting on the prevalence of anxiety and depressive disorders using structured diagnostic interviews and assessed their quality. Pooled pre- and post-injury prevalence estimates of anxiety disorders and depressive disorders were computed. A total of 34 studies described in 68 publications were identified, often assessing anxiety disorders (n = 9), depressive disorders (n = 7), or a combination of disorders (n = 6). Prevalence rates of psychiatric disorders varied widely. Pooled prevalence estimates of anxiety and depressive disorders were 19% and 13% before TBI and 21% and 17% in the first year after TBI. Pooled prevalence estimates increased over time and indicated high long-term prevalence of Axis I disorders (54%), including anxiety disorders (36%) or depressive disorders (43%). Females, those without employment, and those with a psychiatric history before TBI were at higher risk for anxiety and depressive disorders after TBI. We conclude that a substantial number of patients encounter anxiety and depressive disorders after TBI, and that these problems persist over time. All health care settings should pay attention to the occurrence of psychiatric symptoms in the aftermath of TBI to enable early identification and treatment of these disorders and to enhance the recovery and quality of life of TBI survivors.